Seven-part string - Kerr, Thor (Australasian Association of Writing Programs (AAWP), 2021)
Seven-part string is a short story written by Thor Kerr in response to Pangkis, a single channel video artwork by Yee I-Lann (2021). The story, about seven friends who attempt to reconstitute a private bitcoin key, was published in the Meniscus Literary Journal.